2014
DOI: 10.1016/j.mbs.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A poroelastic model for the perfusion of the lamina cribrosa in the optic nerve head

Abstract: In this work we present a mathematical model for the coupling between biomechanics and hemodynamics in the lamina cribrosa, a thin porous tissue at the base of the optic nerve head which is thought to be the site of injury in ocular neurodegenerative diseases such as glaucoma. In this exploratory two-dimensional investigation, the lamina cribrosa is modeled as a poroelastic material where blood vessels are viewed as pores in a solid elastic matrix. The model is used to investigate the influence on the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 40 publications
0
52
0
1
Order By: Relevance
“…This is not biologically accurate as the LC has a thickness of approximately 270 lm. 58 Considering that the LC may exhibit highly heterogeneous stresses (induced by IOP, the retrolaminar pressure, or during eye movements 59 ), it would be logical to observe variations in LC hemodynamics and oxygen concentrations through the thickness of the LC, as predicted by Causin et al 20 LC thickness has also been shown to change with glaucoma progression, which may in turn compromise blood flow further in glaucoma subjects. 8 While using 'surface-like' LCs (as performed herein) should provide a first degree of understanding of LC hemodynamics, future improvements to our models should prioritize on incorporating LC thickness and interactions with LC stresses.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is not biologically accurate as the LC has a thickness of approximately 270 lm. 58 Considering that the LC may exhibit highly heterogeneous stresses (induced by IOP, the retrolaminar pressure, or during eye movements 59 ), it would be logical to observe variations in LC hemodynamics and oxygen concentrations through the thickness of the LC, as predicted by Causin et al 20 LC thickness has also been shown to change with glaucoma progression, which may in turn compromise blood flow further in glaucoma subjects. 8 While using 'surface-like' LCs (as performed herein) should provide a first degree of understanding of LC hemodynamics, future improvements to our models should prioritize on incorporating LC thickness and interactions with LC stresses.…”
Section: Discussionmentioning
confidence: 98%
“…It should be mentioned that a computational study on LC hemodynamics was previously conducted by Causin et al 20 The authors used a poroelastic model, whereby blood capillaries were modeled as homogeneous pores in an elastic matrix. The work accounted for the biomechanical action of IOP, retrolaminar tissue pressure, and scleral tension on hemodynamics, but it did not take into account complex capillary networks and oxygen transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[53], Chapt. 9), because in the present model the variable p is not a Lagrange multiplier (as in the Stokes system), rather, it is the solution of an elliptic Darcy problem (for a similar treatment see [12]). In the case of the ADR equation we employ for the approximation of the concentration and of the cellular volume fractions the primal-mixed finite element discretization scheme with exponential fitting stabilization proposed and investigated in [62].…”
Section: Finite Element Discretizationmentioning
confidence: 99%
“…We utilize the theory of capillary models for porous media [6,28] and we write the porosity at each hierarchical level as…”
Section: Porosity Conductance and Permeabilitymentioning
confidence: 99%